“Omics” Technologies - What Have They Told Us About Uropathogenic Escherichia coli Fitness and Virulence During Urinary Tract Infection? - Torres-Puig, Sergi; García, Vanesa; Stærk, Kristian; Andersen, Thomas E.; Møller-Jensen, Jakob; Olsen, John E.; Herrero-Fresno, Ana (Frontiers in Cellular and Infection Microbiology, 2022)
Uropathogenic Escherichia coli (UPEC) is the main etiological agent of urinary tract infection (UTI), a widespread infectious disease of great impact on human health. This is further emphasized by the rapidly increase in antimicrobial resistance in UPEC, which compromises UTI treatment. UPEC biology is highly complex since uropathogens must adopt extracellular and intracellular lifestyles and adapt to different niches in the host. In this context, the implementation of forefront 'omics' technologies has provided substantial insight into the understanding of UPEC pathogenesis, which has opened the doors for new therapeutics and prophylactics discovery programs. Thus, ‘omics’ technologies applied to studies of UPEC during UTI, or in models of UTI, have revealed extensive lists of factors that are important for the ability of UPEC to cause disease. The multitude of large 'omics' datasets that have been generated calls for scrutinized analysis of specific factors that may be of interest for further selection as vaccine or drug targets. In this review, we describe main UPEC determinants involved in UTI as estimated by 'omics' studies, and we compare prediction of factors across the different 'omics' technologies, with a focus on those that have been confirmed to be relevant under UTI-related conditions. We also discuss current challenges and future perspectives regarding analysis of data to provide an overview and better understanding of UPEC mechanisms involved in pathogenesis which should assist in the selection of target sites for future prophylaxis and treatment.